2014
DOI: 10.1007/s10147-014-0704-4
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Japanese Prostate Cancer Outcome Study of Permanent Iodine-125 Seed Implantation (J-POPS)

Abstract: The J-POPS, a nationwide prospective cohort study that enrolled approximately 40 % of all PI cases in Japan, will provide highly reliable evidence, including outcomes and quality of life, after long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Most of the institutions that participated in this study adopted peripheral loading or modified peripheral loading, which reduces the dose administered to the neighboring urethra. This distribution yields high peripheral doses without substantially increasing the urethral dose (16). Our results are similar to those of Keyes et al (22), who reported that higher dose was associated with higher late urinary toxicity.…”
Section: Urinary Toxicities and Ipsssupporting
confidence: 93%
See 2 more Smart Citations
“…Most of the institutions that participated in this study adopted peripheral loading or modified peripheral loading, which reduces the dose administered to the neighboring urethra. This distribution yields high peripheral doses without substantially increasing the urethral dose (16). Our results are similar to those of Keyes et al (22), who reported that higher dose was associated with higher late urinary toxicity.…”
Section: Urinary Toxicities and Ipsssupporting
confidence: 93%
“…Androgen deprivation therapy was recommended for patients who had prostate volume >40 mL for a short duration and for those who had high-risk disease for several months. The details of the study and the baseline characteristics of the initial subjects who were enrolled to participate in this study from July 2005 to June 2007 have been described by our study group (16).…”
Section: Methods and Materials Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This special situation arises from a general anxiety about radiation risk among the population. Therefore, we usually had to reduce the prostate volume to around 30 cc with NADT for radiation safety (12). Now we can manage to treat a patient with a prostate of 40e60 cc without NADT, following the regulation (22).…”
Section: Discussionmentioning
confidence: 99%
“…About 27,000 cases have been treated with permanent prostate BT in 109 institutions between 2003 and 2013 (12). The 125 I prostate BT program at the Tokyo Medical Center commenced in 2003.…”
Section: Introductionmentioning
confidence: 99%